Energy system impacts of grid tariff structures for flexible power-to-district heat. (1st February 2019) - Sandberg, Eli; Kirkerud, Jon Gustav; Trømborg, Erik; Bolkesjø, Torjus Folsland
Abstract: Flexible use of electricity in district heating has a large potential to integrate an increasing share of renewable energy at a promising benefit-to-cost ratio. The structure of electricity grid tariffs may, however, be a barrier to large-scale implementation. This study analyses how different electricity grid tariff structures affect flexible use of electricity in future Nordic district heating. The energy market model Balmorel is applied for the analysis. The results show that the structure of grid tariffs significantly influence the use of electricity in district heating. Load demand tariffs based on maximum monthly load demand hamper flexible use of electricity in district heating. Going from a high energy charge with no load demand tariff structure to a low energy charge with time-of-use load demand tariff structure increases the power-to-heat share by 60%, increases the wind power generation by 4%, and reduces the CO2 emissions by 7%. A favourable tariff structure can thus encourage more investment in renewable power. This is, however, at the expense of investment in and use of combined heat and power. High electricity prices hamper extensive deployment of flexible electric boilers. With increasing electricity prices, the power-to-heat share will increasingly consist of less flexible heat pumps. Highlights: The design of grid tariffs significantly impact power-to-heat deployment. Monthly settled and fixed load demand tariffs hamper the use of electric boilers. For high electricity prices, the power-to-heat share largely consist of heat pumps. Power-to-heat enables higher integration of wind power, but less cogeneration.